The association of maternal dietary folate intake and folic acid supplementation with small-for-gestational-age births: a cross-sectional study in Northwest China. Issue 4 (5th August 2019) - Li, Shanshan; Liu, Danmeng; Zhang, Ruo; Lei, Fangliang; Liu, Xin; Cheng, Yue; Li, Chao; Xiao, Mengyao; Guo, Leqian; Li, Minmin; Zhang, Binyan; Zhu, Zhonghai; et al.
Abstract: The effect of maternal folate intake on small-for-gestational-age (SGA) births remains inconclusive. The present study aimed to investigate the associations of maternal folate intake from diet and supplements with the risk of SGA births using data from a cross-sectional study in Shaanxi Province of Northwest China. A total of 7307 women who were within 12 months (median 3; 10th–90th percentile 0–7) after delivery were included. Two-level models were adopted to examine the associations of folate (dietary folate, supplemental folic acid and total folate) intake with the risk of SGA births and birth weight Z score, controlling for a minimum set of confounders that were identified in a directed acyclic graph. Results showed that a higher supplemental folic acid intake during the first trimester was negatively associated with the risk of SGA births (≤60 d v . non-use: OR 0·80; 95 % CI 0·66, 0·96; >60 d v . non-use: OR 0·78; 95 % CI 0·65, 0·94; P trend = 0·010; per 10-d increase: OR 0·97; 95 % CI 0·95, 0·99). A higher total folate intake during pregnancy was associated with a reduced risk of SGA births (highest tertile v . lowest tertile: OR 0·77; 95 % CI 0·64, 0·94; P trend = 0·010; per one-unit increase in the log-transformed value: OR 0·81; 95 % CI 0·69, 0·95). A similar pattern was observed for the birth weight Z score. Our study suggested that folic acid supplementation during the first trimester and a higher total folate intake during pregnancy were associated with a reduced risk of SGA births.